2018
DOI: 10.1080/01612840.2018.1445327
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Perceptions of Women Veterans With Military Sexual Trauma

Abstract: The researchers were invited to a transitional home for homeless women veterans to help veterans with body image issues. Convenience sampling was used to recruit 12 veterans who perceived they had a physical difference due to military service. Data were obtained in focus groups where the veterans were invited to share stories. Ricoeur's hermeneutic phenomenology guided the study. The research team learned early in the data collection stage that 11 of the 12 participants suffered military sexual trauma (MST). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The reasons for this fear are unique to each individual. Participants (Freysteinson, Mellott, et al, 2018;Freysteinson, Thomas, Sebastian-Deutsch, et al, 2017) (Freysteinson, Thomas, Thayer, Lelek, & Lee, 2018, 13:01).…”
Section: Ta B L E 1 Mirror Viewing Definitionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reasons for this fear are unique to each individual. Participants (Freysteinson, Mellott, et al, 2018;Freysteinson, Thomas, Sebastian-Deutsch, et al, 2017) (Freysteinson, Thomas, Thayer, Lelek, & Lee, 2018, 13:01).…”
Section: Ta B L E 1 Mirror Viewing Definitionsmentioning
confidence: 99%
“…The reasons for this fear are unique to each individual. Participants (Freysteinson, Mellott, et al, 2018; Freysteinson, Thomas, Sebastian‐Deutsch, et al, 2017) have suggested searching for images of similar disfigurements or having seen a person with a similar disfigurement has led to this fear. Ironically, some individuals have found that the image that was in their mind was far worse than the mirror viewing, resulting in mild mirror discomfort.…”
Section: Mirror Viewing Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Buhl-Nielsen (2006) found that adolescents with personality disorders were more dysregulated during the mirror interview—a semistructured interview assessing embodied cognition of the self—expressing alienation from their bodies and in some cases a lack of recognition of their reflection in the mirror. Female veterans with military sexual trauma have reported feeling similarly estranged from their reflections when looking in the mirror (Freysteinson et al, 2018). Although not identified as such in either study, the participants were describing depersonalization, a specific type of dissociation characterized by a disconnection from the self or body (Rabellino et al, 2016).…”
mentioning
confidence: 99%